9-cis-Epoxycarotenoid dioxygenase as a switch of immunityrelated signalling pathways in Solanum lycopersicum plants - Stepanova, Elizaveta S.; Kukresh, Glafira V.; Nikolaichik, Yevgeny A.; Kalubaka, Nastassia V. (Experimental Biology and Biotechnology, 2024)
It has been established that reduced expression of the NCED3 gene causes a decrease in the size of Solanum lycopersicum plants and increases their susceptibility to Pectobacterium versatile infection. A change in the expression of salicylate signalling genes was revealed: the expression of the genes for the signalling protein NPR5 and the pathogenesis-related protein PR1a increased. It was also noted that the expression of the genes for the pathogenesis-related proteins PR3, PR5, PR10 and the transcription factor WRKY65 increased, and the expression of the gene for the pathogenesis-related protein PR2 became sensitive to the pathogen strain. Based on the results obtained, it was suggested that the NCED3 gene provides resistance to pectobacteriosis in tomato plants by inhibiting the salicylate signalling pathway, leading to activation of the hypersensitive response.
Keywords: 9-cis-epoxycarotenoid dioxygenase; Solanum lycopersicum; Pectobacterium versatile; plant immunity